2009
DOI: 10.1261/rna.1702009
|View full text |Cite
|
Sign up to set email alerts
|

Deep sequencing identifies new and regulated microRNAs in Schmidtea mediterranea

Abstract: MicroRNAs (miRNAs) play important roles in directing the differentiation of cells down a variety of cell lineage pathways. The planarian Schmidtea mediterranea can regenerate all lost body tissue after amputation due to a population of pluripotent somatic stem cells called neoblasts, and is therefore an excellent model organism to study the roles of miRNAs in stem cell function. Here, we use a combination of deep sequencing and bioinformatics to discover 66 new miRNAs in S. mediterranea. We also identify 21 mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
53
0
2

Year Published

2010
2010
2013
2013

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 22 publications
3
53
0
2
Order By: Relevance
“…It was previously reported that mature miRNAs from the sme-miR-71b/2d/752/13 miRNA cluster were expressed in neoblast populations (Friedländer et al 2009;Lu et al 2009). Interestingly, we found that miR-71b and miR-13 were enriched in both the X1 and X2 cell populations, while sme-miR-2d-3p was enriched in the X2 population (Fig.…”
Section: Deep Sequencing Of Small Rnas From Regenerating Tissue and Nmentioning
confidence: 95%
See 4 more Smart Citations
“…It was previously reported that mature miRNAs from the sme-miR-71b/2d/752/13 miRNA cluster were expressed in neoblast populations (Friedländer et al 2009;Lu et al 2009). Interestingly, we found that miR-71b and miR-13 were enriched in both the X1 and X2 cell populations, while sme-miR-2d-3p was enriched in the X2 population (Fig.…”
Section: Deep Sequencing Of Small Rnas From Regenerating Tissue and Nmentioning
confidence: 95%
“…Previously, it was reported that let-7a and let-7b were enriched in neoblasts (Friedländer et al 2009;Lu et al 2009). Interestingly, our study revealed that let-7a and let-7b show fold-change enrichment in the X2 population (X1: 1.004, X2: 1.429, Xins: 0.56), which predominantly contains neoblast progeny rather than proliferating neoblasts (X1) and differentiated cells (Xins).…”
Section: Deep Sequencing Of Small Rnas From Regenerating Tissue and Nmentioning
confidence: 99%
See 3 more Smart Citations